2019
DOI: 10.1055/s-0039-1693699
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Surgery in Breast Reconstruction: A Systematic Review

Abstract: Background Enhanced Recovery after Surgery (ERAS) principles have received focused attention in breast reconstruction. Many protocols have been described in the literature for both autologous and alloplastic reconstruction. This systematic review serves to better characterize successful ERAS protocols described in the literature for potential ease of adoption at institutions desiring implementation. Methods A systematic review of ERAS protocols for autologous and alloplastic breast reconstruction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…In the United Kingdom, autologous breast reconstruction has an average length of stay of 5 days 24,25 . The recent utilisation of enhanced recovery protocols (ERAS) by high-volume centres have revolutionised how microsurgical breast reconstruction is managed in the perioperative period 7 . A key aim of enhanced recovery protocols (ERAS) is reducing the length of hospital stay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United Kingdom, autologous breast reconstruction has an average length of stay of 5 days 24,25 . The recent utilisation of enhanced recovery protocols (ERAS) by high-volume centres have revolutionised how microsurgical breast reconstruction is managed in the perioperative period 7 . A key aim of enhanced recovery protocols (ERAS) is reducing the length of hospital stay.…”
Section: Resultsmentioning
confidence: 99%
“…A key aim of enhanced recovery protocols (ERAS) is reducing the length of hospital stay. Recent publications of enhanced recovery protocols from well-established large volume centres have demonstrated a median length of stay between 4-7 days [4][5][6][7][8][9][10][11]26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, multimodal analgesic protocols are likely to become more commonly implemented in breast reconstruction recovery protocols, particularly with the increased utilization of ERAS protocols in hospital systems. 49 Based on a recent systematic review on ERAS implementation in breast reconstruction, 49 across 11 different studies analyzed demonstrated enhanced patient experience and improved outcomes by reducing LOS and opioid use, without compromising successful reconstructive outcomes. The most effective elements to enhance patient recovery following autologous or alloplastic breast reconstruction included: patient counseling and education, limited preoperative fasting, appropriate thromboprophylaxis and antibiotic prophylaxis, preoperative antiemetics, multimodal analgesia and use of local anesthetic, goal-directed intravenous fluid management, prompt removal of drains and catheters, early diet advancement, and encouragement of early ambulation.…”
Section: Enhanced Recovery After Surgery and Multimodal Approachesmentioning
confidence: 99%
“…Previous studies have analyzed the efficacy of various enhanced recovery after surgery (ERAS) protocols in microsurgical, DIEP, and alloplastic breast reconstruction cases. [28][29][30] This study aims to evaluate outcomes with this particular DIEP pathway to assess its safety and feasibility in clinical practice at a major academic medical center.…”
mentioning
confidence: 99%